Mental health help-seeking intentions and organizational climate among military members. Issue 4 (4th July 2019) - Cuyler, Mishaw; Guerrero, Laura
ABSTRACT: The psychological effects of war include anxiety, depression, alcohol misuse and Post-Traumatic Stress Disorder (PTSD). Military members that displayed symptoms of mental illness were thought to lack the strength and courage necessary to be soldiers. As a result, many military members who suffered from these symptoms would not seek help for mental health care. This paper investigates the mental health help-seeking intentions of military members using the Theory of Planned Behavior (TPB) and the role of leadership support climate and coworker support climate. This paper contributes to the literature in three ways. First, this paper applies a rigorously tested theoretical framework to the study of mental health help-seeking intentions in military members. Second, this paper incorporated the constructs of leadership support climate and coworker support climate into mental health help-seeking literature. Third, this paper introduces the concepts of leadership support climate and organizational support climate into the study of the theory of planned behavior. This study found that the personal attitudes of military members towards mental health help-seeking are positively related to their mental health help-seeking intentions. The study also found that mental health help-seeking attitudes mediated the relationship between leadership support climate and mental health help-seeking intentions. These results underscore the important role of leaders in setting a supportive organizational climate and influencing military members to seek help for mental health problems.